2012
DOI: 10.1021/cs300032n
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced Surface Sensitivity of Hydroxylamine Oxidation on Gold Single-Crystal Electrodes in Acidic and Neutral Aqueous Solutions

Abstract: The oxidation of hydroxylamine on the three low index faces of Au single crystal has been investigated by cyclic voltammetry in buffered aqueous solutions in the pH range 1–7 under quiescent conditions. The results obtained have shown that the onset potential for the reaction on Au(100) is more negative, and the current in the region of small overpotentials is higher than for Au(110) and Au(111) regardless of the pH of the solution. Measurements performed in phosphate buffer (pH 7) with single crystal rotating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Note that this band corresponds to a dissolved species, as DFT calculations have shown that isocyanic acid interacts very weakly with gold surfaces [27]. Regarding hydroxylamine, recent results by Scherson's group show that this species readily oxidizes above 0.50 V SCE on gold electrodes in HClO4 solutions [35]. In situ infrared by the same group proved the formation of N2O as witnessed by a band at 2230 cm -1 [28], similar to that in Figure 2.…”
Section: Resultssupporting
confidence: 64%
“…Note that this band corresponds to a dissolved species, as DFT calculations have shown that isocyanic acid interacts very weakly with gold surfaces [27]. Regarding hydroxylamine, recent results by Scherson's group show that this species readily oxidizes above 0.50 V SCE on gold electrodes in HClO4 solutions [35]. In situ infrared by the same group proved the formation of N2O as witnessed by a band at 2230 cm -1 [28], similar to that in Figure 2.…”
Section: Resultssupporting
confidence: 64%
“…[3] Further evidence of an adsorbed species was obtained from differences in the rates constants for the reaction for the low index faces of Au single crystal as measured with rotating disk electrodes. [13] As the Au oxide is reduced, the presumably bare Au surface acquires very high activity toward NH 2 OH oxidation yielding, within the time scale of the measurements, currents which exceed those found during the scan toward positive potentials, as clearly seen in Figure 5 above.…”
Section: Resultsmentioning
confidence: 62%
“…rotating disk electrode techniques for the low index faces of Au single crystal. [13] As mentioned in the Introduction the most likely species based on the in situ SERS data reported in a previous communication is NO 2 (ads). [3] Further evidence of an adsorbed species was obtained from differences in the rates constants for the reaction for the low index faces of Au single crystal as measured with rotating disk electrodes.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…To the best of our knowledge, the oxidation current density of 14.65 mA/cm 2 obtained in this experiment is the highest value among those measured in the same media using Au-based electrodes, including self-supported nanoporous Au film electrodes [11], polycrystalline Au electrodes [13], and nanoporous Au electrodes prepared by dealloying Au-Ag [10]. The excellent catalytic activity of the Au NPs can be attributed to the combination of their clean surfaces [21,728, facets well-arranged by the Au (111) plane [69,70], and intimate contact with the FTO substrate. Consequently, we expect that this Au NS-based electrode can be a versatile tool for various catalytic and electrochemical applications.…”
Section: Resultsmentioning
confidence: 92%